Research on the Economics of Cancer-Related Health Care: An Overview of the Review Literature. Issue 59 (5th July 2022) - Davidoff, Amy J; Akif, Kaitlin; Halpern, Michael T
Abstract: We reviewed current literature reviews regarding economics of cancer-related health care to identify focus areas and gaps. We searched PubMed for systematic and other reviews with the Medical Subject Headings "neoplasms" and "economics" published between January 1, 2010, and April 1, 2020, identifying 164 reviews. Review characteristics were abstracted and described. The majority (70.7%) of reviews focused on cost-effectiveness or cost-utility analyses. Few reviews addressed other types of cancer health economic studies. More than two-thirds of the reviews examined cancer treatments, followed by screening (15.9%) and survivorship or end-of-life (13.4%). The plurality of reviews (28.7%) cut across cancer site, followed by breast (20.7%), colorectal (11.6%), and gynecologic (8.5%) cancers. Specific topics addressed cancer screening modalities, novel therapies, pain management, or exercise interventions during survivorship. The results indicate that reviews do not regularly cover other phases of care or topics including financial hardship, policy, and measurement and methods.